CONDITIONS FOR THE CONVERGENCE OF BRANCHING PROCESSES WITH IMMIGRATION STARTING FROM A LARGE NUMBER OF PARTICLES - H. K. Zhumakulov (Galaxy International Interdisciplinary Research Journal, 2022)
In this section, we study sufficient conditions for the convergence of a sequence of almost critical Galton -Watson branching processes with uniform immigration starting from a large number of particles.